The other Zions : the lost histories of Jewish nations - Maroney, Eric (Rowman & Littlefield Publishers, 2010)
Though Israel is the only Jewish nation most people can name, there have been many more. Author Eric Maroney introduces readers to the Jews of Khazaria, Adiabene (modern day Iraq), Ethiopia, Birobidzhan (modern day Russia), Himyar (modern day Yemen), and more. --from publisher description.